Первые находки коралловых построек в раннем карбоне Львовского палеозойского прогиба - Шульга, В.Ф.; Огарь, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Organic buildups (biostromes and bioherms) in the coal formation of the Lvov Palaeozoic Trough are described for the first time. The primary framework builders were the colonial rugose corals. The coral buildups were formed in a shallow water environment and located within the tectonically active area. It is a narrow stripe of 10 - 12 km in width and more than 70 km in length. The late Visean coral bioherms and biostromes under consideration resemble those from some regions of Western Europe.